"Renal Cell Carcinoma With Leiomyomatous Stroma" Harbor Somatic Mutations of TSC1, TSC2, MTOR, and/or ELOC (TCEB1): Clinicopathologic and Molecular Characterization of 18 Sporadic Tumors Supports a Distinct Entity. (16th May 2020) - Shah, Rajal B.; Stohr, Bradley A.; Tu, Zheng Jin; Gao, Yuan; Przybycin, Christopher G.; Nguyen, Jane; Cox, Roni M.; Rashid-Kolvear, Fariborz; Weindel, Michael D.; Farkas, Daniel H.; Trpkov, Kiril; McKenney, Jesse K.
Abstract : Renal cell carcinoma with (angio) leiomyomatous stroma (RCCLMS) is included as a provisional entity in the 2016 World Health Organization (WHO) classification of renal epithelial neoplasia; however, debate remains whether it represents a distinct entity or a heterogenous group of renal cell carcinomas (RCCs) with overlapping morphology. Also, its relationship to similar tumors occurring in the setting of tuberous sclerosis complex (TSC) is not fully addressed. We analyzed the clinicopathologic, immunohistochemical, and molecular characteristics of 23 sporadic RCCs associated with smooth muscle stroma and classified them into 2 groups, independent of molecular results: (1) RCCLMS (n=18) and (2) clear cell renal cell carcinoma (CCRCC) (n=5). The classification of a case as "RCCLMS" was based on morphologic comparison with 5 "index" RCCs from 3 patients with TSC showing similar features and the presence of diffuse CK7 expression. To investigate mutational and copy number alterations, a 170-gene solid tumor panel was utilized to sequence 14 RCCLMSs and control of 5 CCRCCs. Also, 4 RCCLMSs, suspicious for chromosome 8 monosomy, were further evaluated by a broader 479 gene sequencing panel that included ELOC (also referred to as TCEB1 ). Clinical information and follow-up data were obtained from electronic medical records. The mean age of patients with RCCLMS was 52 years (range, 33 to 69) with male:female ratio of 1:2. Macroscopically, all tumors were solitary and predominantly (82%) tan/red, circumscribed, and solid. The average tumor size was 2.3 cm (range, 1.1 to 4.5). Microscopically, the distinctive feature included tumor nodules of elongated and frequently branching tubules lined by cells with voluminous clear to mildly eosinophilic cytoplasm (100%), separated by focal to prominent smooth muscle stroma. Additional frequently identified features included: biphasic pattern of collapsed acini surrounding tubules with voluminous cytoplasm (50%), focal papillary architecture (39%), peritumoral lymphoid aggregates (39%), and hemosiderin-laden macrophages (33%). All 11 (100%) RCCLMSs with available staging information were pT1; 78% were WHO/International Society of Urologic Pathology (ISUP) grade 2 and 22% grade 3. Immunophenotypically, RCCLMSs were characterized by diffuse CK7, CAM5.2 and CD10 reactivity (100%). All patients with available follow-up (n=10) were alive and without disease progression after a mean and median follow-up of 25.2 (range: 1 to 58) and 25 months, respectively. The molecular results showed recurrent mutations in all RCCLMS: TSC1 (4), TSC2 (4), MTOR (6), and/or ELOC (2). Five control CCRCCs demonstrated primary alterations in VHL gene, while all 14 RCCLMS cases tested had intact VHL gene. Of 2 RCCLMSs with confirmed monosomy 8, 1 showed a hotspot ELOC mutation without TSC/MTOR mutations, and 1 showed a previously undescribed 3-bp in-frame ELOC deletion, along with a truncating TSC1 mutation. In conclusion, RCCLMS, as defined herein, harbors recurrent mutations of TSC1 / TSC2, MTOR, and/or ELOC, consistent with hyperactive MTOR complex. Our findings argue that these tumors represent the sporadic counterpart to morphologically identical tumors occurring in TSC patients. Finally, the data support that RCCLMS is a novel subtype of RCC with unique morphologic, immunohistochemical, and molecular characteristics that is distinct from CCRCC and clear cell-papillary RCC.